2020
DOI: 10.21203/rs.3.rs-29717/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated Puncture Score: Force-Displacement Weighted Rind Penetration Tests Improve Stalk Lodging Resistance Estimations in Maize

Abstract: Background: Stalk lodging (breaking of agricultural plant stalks prior to harvest) is a multi-billion dollar a year problem. Rind penetration resistance tests have been used by plant scientists and breeders to estimate the stalk lodging resistance of maize for nearly a hundred years. However, the rind puncture method has two key limitations: (1) the predictive power of the test decreases significantly when measuring elite or pre-commercial hybrids, and (2) using rind penetration measurements as a breeding me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that stalk mechanical strength can be used as an important index to predict lodging risk, and that bending strength and rind penetrometer resistance (RPR) can reflect stalk mechanical strength (Zhang et al, 2019). A combination of crushing strength, rind penetrometer resistance (RPR), and bending strength has been used to determine the relationship between stalk mechanical strength and lodging (Stubbs et al, 2020;Wang et al, 2020;Shao et al, 2021). In a recent study, we have demonstrated that rind penetrometer resistance (RPR) and breaking force can be used to determine the mechanical strength of sugarcane stalks (Shen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that stalk mechanical strength can be used as an important index to predict lodging risk, and that bending strength and rind penetrometer resistance (RPR) can reflect stalk mechanical strength (Zhang et al, 2019). A combination of crushing strength, rind penetrometer resistance (RPR), and bending strength has been used to determine the relationship between stalk mechanical strength and lodging (Stubbs et al, 2020;Wang et al, 2020;Shao et al, 2021). In a recent study, we have demonstrated that rind penetrometer resistance (RPR) and breaking force can be used to determine the mechanical strength of sugarcane stalks (Shen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%